The influence of transformational leadership and readiness for change on followers' performance in public higher education institutions in Malaysia - R. chitara, Ramasamy (2019)
Public higher education institutions (PHEI) worldwide are subjected to growing commercialization of higher education. They are unable to shield themselves from the intrusion of marketplace values onto the sacred ground of "public good". Traditionally, PHEI were seen as national institutions providing a valuable contribution to society and therefore worthy of support. However, of late, it is increasingly being challenged as the provision of knowledge becomes just another commercial transaction. Thus, there is a growing demand for PHEI to think more like businesses and less like educational institutions. The urgent scrutiny into PHEI performance has given way for opportunities into followers' performance- based research. This study investigated transformational leadership, readiness for change and followers' performance since they are catalysts for PHEI performance. The Social Exchange Theory, the Transformational Leadership Theory, and the Change Model underpinned this study framework. This quantitative study was carried out in all the twenty Malaysian PHEI. An online questionnaire was administered to the heads of departments, from all these universities, who were selected using the proportioned stratified random sampling. The four main hypotheses of this study were tested using the Smart PLS 3.0 software. The results of the study found significant positive effects of transformational leadership and readiness for change on followers' performance. In addition, readiness for change was found to have a significant mediating effect on the relationship between transformational leadership and followers' performance. This study gives new insight to the management of PHEl about the importance of developing transformational leadership as well as acknowledging the serious impact brought by transformational leadership on followers' performance. The results of the study also foreshadowed the crucial effect of readiness for change; as an element needed to build readiness, influencing strategies being developed, injecting 'urgency', and lastly the need for readiness involvement in various interventions.